ESKALASI KOMITMEN DAN PROJEK BERISIKO: PERUBAHAN RASIONALITAS DALAM GRUP - Viona Christalia Nugrahanti; Intiyas Utami; Ika Kristianti (Jurnal Akuntansi, 2018)
This study aims to provide empirical evidence of how the decision taken by the manager if it is in the condition of escalation of commitment and faced with a risky project. The research was conducted at Satya Wacana Christian University with students majoring in Accounting, Faculty of Economics and Business. 77 participants were incorporated in the study who acted as production managers and taken 59 to become ready-to-process data. Manipulation is done in the form of high and low commitment escalation, and high-risk and low-risk projects. The experimental method was chosen to examine the causality relationship between escalation of commitment, risk project, and change of rationality by applying cost accounting concepts that have been studied during college. The results show that when participants are in a condition of low commitment escalation and face a low-risk project, it will make rational decisions. The same was also shown after the participants discussed in the group. The smallest change of rationality is generated after the participants have a discussion in the group. This study contributes to the accounting science of how cost accounting is applied to decision making and also contributes to the business world especially for decision makers. Decision makers can consider escalating commitments and risky projects that can alter their rationality.Keywords: escalation of commitment, risk project, rationality, group